Analysis of the Influence of Marketing Strategy Towards Branding and Positioning at Kupang Public Heatlh Center Sub-Regency Jetis, Mojokerto Year 2018 - Mohamad Thoha; Koesnadi Koesnadi; Byba Melda Suhita (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Not all nurses are able to carry out its The more the community capitalize on inpatient services inpatient Clinics. Meanwhile, capabilities and resources at the level of clinics such as number of physicians, dentists have still not been adequately, even a specialist very minimal amount. Facilities and means of medical lainpun is still very limited in number. This condition causes the health services inpatient clinics can not maximum. The goal of research to analyze the effect of marketing strategy effect on branding and positioning. Design research analytical quantitative approach with IE. Research variables namely marketing strategy as the independent variable. Branding and potitioning as the dependent variable. This research population were al off patient at Kupang public health center of Sub-regency Jetis, Mojokerto at October 15th – November 15th, 2018. Samples taken with the technique of simple random sampling as much as 93 respondents. Data is collected with instruments ceklist and processed in coding, editing, tabulating and scoring as well as tested with linear regression test. Linear regression results indicate that partially and simultaneously the value of p values < 0.05 so that there were marketing strategies influence branding and potitioning. On the branding components of place does not affect the branding and price does not affect potitioning. Marketing strategy implemented by the management of clinics are able to make Mussel communities receive good service so that the community give its own assessment of the branding or for services provided by the clinic